2015
DOI: 10.2147/ceor.s74181
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the importance of predictors in unplanned hospital readmissions for chronic obstructive pulmonary disease

Abstract: PurposeThe all-cause readmission rate within 30 days of index admissions for chronic obstructive pulmonary disease (COPD) was approximately 21% in the United States in 2008. This study aimed to examine patient and clinical characteristics predicting 30-day unplanned readmissions for an initial COPD hospitalization and to determine those predictors’ importance.Patients and methodsA retrospective study was conducted in patients with COPD-related hospitalizations using commercial claims data from 2010 to 2012. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
2
34
1
2
Order By: Relevance
“…Furthermore, a retrospective study in the USA using commercial claims data observed that COPDSS was an important predictor of 30-day unplanned readmission. 35 However, we could not find a significant predictive value of COPDSS for the composite event in our population. A reason for this discrepancy could be at least in part the selection of our population, because exacerbation history and management have a high impact in COPDSS.…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore, a retrospective study in the USA using commercial claims data observed that COPDSS was an important predictor of 30-day unplanned readmission. 35 However, we could not find a significant predictive value of COPDSS for the composite event in our population. A reason for this discrepancy could be at least in part the selection of our population, because exacerbation history and management have a high impact in COPDSS.…”
Section: Discussioncontrasting
confidence: 70%
“…In a study of hospital readmissions for chronic medical conditions in Denmark and in the US Kaiser Permanente system from 2002 to 2007, all-cause 30-day readmission rates after a COPD hospitalization ranged from 20.7 to 24.1 % in Denmark, and from 19.4 to 21.4 % in Kaiser Permanente [ 23 ]. Another study of US claims data, using an analysis approach similar to ours, also found that factors associated with COPD severity at baseline (e.g., oxygen therapy, respiratory medicine use, and pulmonologist visits) were predictors of COPD-related readmission within 30 days [ 24 ].…”
Section: Discussionmentioning
confidence: 84%
“…The clinical characteristics reflect those of the stable patients, with more comorbidities, worse prognosis, and suboptimal therapy (61)(62)(63)(64). Unrecognized chronic HF is present in a substantial number of patients hospitalized for ECOPD (65), may be a precipitating factor, and may hinder weaning from mechanical ventilation (66), conferring an overall poor prognosis (67).…”
Section: Clinical Characteristics and Diagnostic Challengesmentioning
confidence: 99%